Cost‐efficient design methodology for compact rat‐race couplers. Issue 3 (17th September 2014) - Koziel, Slawomir; Kurgan, Piotr; Pankiewicz, Bogdan
ABSTRACT: In this article, a reliable and low‐cost design methodology for simulation‐driven optimization of miniaturized rat‐race couplers (RRCs) is presented. We exploit a two‐stage design approach, where a composite structure (a basic building block of the RRC structure) is first optimized using a pattern search algorithm, and, subsequently, the entire coupler is tuned by means of surrogate‐based optimization (SBO) procedure. SBO is executed with the underlying low‐fidelity model implemented as cascaded response surface approximations (RSAs) of the composite structure. Full‐wave analysis of the entire coupler is required at the tuning stage only. By combining SBO with coupler decomposition and RSA surrogates, the overall cost of the design process corresponds (in terms of CPU time) to less than three electromagnetic simulations of the compact RRC, and results in highly miniaturized structure (82% footprint reduction compared to conventional coupler) that exhibits perfect return loss and isolation (almost −60 dB at the operating frequency), as well as a strong harmonic and spurious suppression (below −20 dB) in, approximately, 3–9.5 GHz frequency band. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:236–242, 2015.